2019
DOI: 10.1055/s-0039-1688529
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Analysis of Proximal End of the Tibia

Abstract: Background Total knee arthroplasty and unicompartmental knee arthroplasty are frequently done procedures for the treatment of various forms of arthritis and knee injuries. The knee prosthesis, which is used for these procedures, requires adequate sizing specific to the population. Morphometric parameters of upper end of the tibia can be used to guide treatment and monitor outcome of total knee replacement surgeries. Information regarding morphometry of upper end of the tibia is important as it provides reliabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
0
3
Order By: Relevance
“…The study in Korean population 10 revealed the dimension of anteroposterior measurement of intercondylar area of tibia to be 47.3+3.8mm as compared to 48.79±0.76mm in the present study. However, the results of the studies done on Indian population 13,15 were lower than the present study. The mediolateral measurement across both tibial condyles in the present study corroborate with the studies done on Thai population 12 and Indian population 15 However, higher values were reported in Korean population 10 and Chinese population.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…The study in Korean population 10 revealed the dimension of anteroposterior measurement of intercondylar area of tibia to be 47.3+3.8mm as compared to 48.79±0.76mm in the present study. However, the results of the studies done on Indian population 13,15 were lower than the present study. The mediolateral measurement across both tibial condyles in the present study corroborate with the studies done on Thai population 12 and Indian population 15 However, higher values were reported in Korean population 10 and Chinese population.…”
Section: Discussioncontrasting
confidence: 92%
“…However, the results of the studies done on Indian population 13,15 were lower than the present study. The mediolateral measurement across both tibial condyles in the present study corroborate with the studies done on Thai population 12 and Indian population 15 However, higher values were reported in Korean population 10 and Chinese population. 11 Designing the prosthesis of knee, considering the gender difference has been advocated in Chinese population.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation